Perancangan Sistem Multi Computer Numerical Control (CNC) untuk Plotter dan Laser Engraving - Diki Muhamad Sobirin; Jana Utama (Komputika : Jurnal Sistem Komputer, 2020)
ABSTRACT – The purpose of this research is to make CNC which has 2 functions in 1 system. By utilizing a USB serial for communication between a computer and a microcontroller. To operate CNC, the program is designed using LabVIEW software, the program will convert images into G-Code and send G-Code into the CNC system to do the plotter or laser engraving process. CNC plotter can make an image pattern on paper with a ballpoint pen automatically. Whereas CNC Laser Engraving can make a engraving on wood by utilizing laser heat, laser heat will erode the surface of the wood automatically. In designing multi CNC, 2 stepper motors are used as the axis actuator , and for the ballpoint pen drive uses a servo motor. The laser used for wood engraving uses a 500 mw laser diode. Based on the test results in this study, the program at LabVIEW can convert images into G-Code lasers, then the program send G-Codes into a CNC system, as the result CNC can process laser engraving on wood as well as set the thickness of the engraving as the need. The ideal feedrate is 50-500 mm / minute and the maximum is 2000 mm / minute. On the other hand, CNC Plotter is able to print a square shape image with the smallest size of 2 mm x 2 mm, and the circle with the smallest diameter of 2 mm with a 100% accuracy rate. The maximum dimensions of images that can be done by Multi CNC are 300 mm x 300 mm. Keywords – Multi CNC, LabVIEW, G-Code, Microcontroller.